Patterns of Demand and Provision in English Adult Social Care Services. (1st February 2022) - Hood, Rick; Goldacre, Allie; Abbott, Simon; Jones, Ray
Abstract: This article reports on a quantitative study of the national datasets for adult social care in England. Building on recent analysis of trends in demand and expenditure, the aim of the study was to investigate the relationship between local authority (LA) characteristics, levels of demand for state-funded services and rates of short- and long-term provision. Publicly available data on short- and long-term activity and finances were collected for all LAs in England from 2016 to 2019 and combined with other indicators including population demographics and the Index of Multiple Deprivation. Correlation analysis was undertaken to investigate patterns of demand and provision and their link to contextual factors. Findings showed that variation between LAs was to some extent shaped by contextual factors such as deprivation and demographics, but was also subject to the effects of rationing and the impact of the self-funded market on levels of demand. Implications are discussed for efforts to reform the adult social system and address longstanding inequalities that have been both highlighted and exacerbated by the COVID-19 pandemic. Abstract : Little is known about the factors driving variation in adult social care provision between local authorities in England. This study investigates those factors, including the effect of deprivation and population demographics on the provision of short-term care and long-term support. The findings give an insight into the impact of rationing and the operation of inequalities in the system.